The Influence of Non-Financial Compensation and Workload on Employee Turnover Intention PT. Megah Abadi Estate - Mitha Cahyani; Hamid Halin; Emilda Emilda (ProBisnis : Jurnal Manajemen, 2023)
This study aims to analyze the effect of Non-Financial Compensation and Workload on Employee Turnover Intention of PT Majestic Eternal Estate Totaling 40 employees. Data collected through questionnaires and analyzed using multiple linear regression method. The results showed that partially Non-Financial Compensation has an effect on Employee Turnover Intention. Conversely, workload has no effect on employee turnover intention. Simultaneously, Non-Financial Compensation and Workload affect Employee Turnover Intention. This empirical finding is useful for PT Majestic Eternal Estate. Company leaders should pay attention to Non-Financial Compensation and Workload in company management because these two factors affect Employee Turnover Intention.